Pradinių ir galinių priebalsių derinimas veiksmažodio šaknyse - Kruopienė, Irena (Kalbotyra, 2001)
The article presents a synchronic analysis of verb root sound structure in Standard Lithuanian. More than half of verb roots analysed combined two (sometimes three) consonants of the same subclass. Sonarants were more frequent in the alternating nucleus roots, while plosives predominated in the stable nucleus roots. Plosives and fricatives are quite frequently combined according to the opposition voiced vs. voiceless. In both verb groups voiceless combinations predominated.